Ternary small molecule solar cells exhibiting power conversion efficiency of 10.3%. (September 2017) - Zhang, Miao; Wang, Jian; Zhang, Fujun; Mi, Yang; An, Qiaoshi; Wang, Wenbin; Ma, Xiaoling; Zhang, Jian; Liu, Xinfeng
Abstract: The elaborately prepared BTR:PC71 BM based small molecule solar cells (SMSCs) exhibit a champion power conversion efficiency (PCE) of 9.37%, which should be among the highest values for previous reports on BTR:PC71 BM based SMSCs. Based on the optimized binary SMSCs, small molecule DIB-SQ was selected as the third component to fabricate ternary SMSCs. The champion PCE of 10.3% was achieved for ternary SMSCs with 6 wt% DIB-SQ in donors. An approximate 10% PCE improvement was obtained due to obviously increased short current density ( J SC ) of 15.44 mA/cm 2 and fill factor (FF) of 73.8%. The main contribution of DIB-SQ can be summarized as the enhanced photon harvesting in long wavelength range and the optimized phase separation for better exciton dissociation and charge transport in ternary active layer. The results further demonstrate that ternary strategy should be an efficient and versatile method to improve the performance of SMSCs. Graphical abstract: Highlights: The BTR: PC71 BM based SMSCs exhibit high PCE of 9.37% compared with previous reports. The PCE of ternary SMSCs approaches 10.3% by incorporating 6 wt% DIB-SQ in donors. The PCE of 10.3% is among the highest value for ternary SMSCs up to date. Photon harvesting and morphology can be co-optimized by incorporating 6 wt% DIB-SQ.